Intravascular Therapy Techniques for Acute Arterial Occlusion - علي, سليمان (Latakia University Journal -Medical Sciences Series, 2020)
The techniques of opening the arteries through the skin have evolved considerably in comparison with the pharmacological and surgical treatments of arterial occlusion.